When Corporations Rule the WorldWhen Corporafions fluie fhe Worid, by Korten David C.. Berrett-Koehler, 1995. - Ryland, Elisabeth (Academy of Management Review, 1997)
The article reviews the book ?When Corporations Rule the World,? by David C. Korten.